THE ANXIETY OF EFL PRE-SERVICE TEACHERS WHEN CONDUCTING MICRO-TEACHING SESSIONS AT UNIVERSITY OF FOREIGN LANGUAGE STUDIES – THE UNIVERSITY OF DANANG (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The current paper investigates EFL pre-service teachers’ anxiety when carrying out the micro-teaching sessions with a view to finding out the causes of the anxiety, the negative impacts of anxiety on EFL pre-service teachers and some suggestions to reduce EFL pre-service teachers’ anxiety when conducting the micro-teaching sessions. 40 EFL pre-service teachers who are currently fourth-year students at the Faculty of Foreign Language Teacher Education, University of Foreign Language Studies – the University of Danang took part in the study by filling in the questionnaires. Simultaneously, 10 out of 40 participants also participated in the interviews. The findings revealed that “not managing the time”, “teaching productive skills (writing and speaking)”, “encountering technical problems” are major anxiety-inducing causes. The negative influences of anxiety on their teaching performance were identified, especially not arousing the classroom atmosphere and other pre-service teachers’ curiosity in the warm-up section. The researcher has also suggested some suggestions so as to minimize teaching anxiety and ameliorate the effectiveness of micro-teaching technique.